Analisis Kinerja dan Peningkatan Kualitas Enterprise Resource Planning (ERP) dengan Metode Servqual dan Six Sigma - Esa, Mohammad Zaqi; Wasesa, Andarmadi Jati Abdhi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research analyzes the quality of Enterprise Resource Planning services at the PT CMPI ice cream factory using the Servqual and Six Sigma methodology. The main objective of this research is to identify the level of satisfaction and causes of user dissatisfaction with the Enterprise Resource Planning service, and determine efforts to improve service quality that require improvement. Primary data was obtained by distributing questionnaires to 43 respondents who had used Oracle's Enterprise Resource Planning services more than once in the company and testing them in validity and reliability tests. Servqual and Six Sigma methods are applied for problem analysis and solving problems. The results of the Servqual analysis, the average value of gap 5 is -0.591, meaning that users at PT CMPI are not satisfied with the services provided by the Oracle ERP provider vendor. Use of DPMO (Defect Per Million Opportunity) average value of 137,874 and sigma value of 2.74 to identify problems that will be analyzed using Pareto Diagrams and Fishbone Diagrams to uncover the root of the problem.